Association of retinal nerve layers thickness and brain imaging in healthy young subjects from the i‐Share‐Bordeaux study - Lima Rebouças, Sara Cristina; Crivello, Fabrice; Tsuchida, Ami; Tzourio, Christophe; Schweitzer, Cédric; Korobelnik, Jean‐François; Delcourt, Cécile; Helmer, Catherine (Human brain mapping, 2023)
Given the anatomical and functional similarities between the retina and the brain, the retina could be a “window” for viewing brain structures. We investigated the association between retinal nerve fiber layers (peripapillary retinal nerve fiber layer, ppRNFL; macular ganglion cell‐inner plexiform layer, GC‐IPL; and macular ganglion cell complex, GCC), and brain magnetic resonance imaging (MRI) parameters in young health adults. We included 857 students (mean age: 23.3 years, 71.3% women) from the i‐Share study. We used multivariate linear models to study the cross‐sectional association of each retinal nerve layer thickness assessed by spectral‐domain optical coherence tomography (SD‐OCT) with structural (volumes and cortical thickness), and microstructural brain markers, assessed on MRI globally and regionally. Microstructural MRI parameters included diffusion tensor imaging (DTI) and Neurite Orientation Dispersion and Density Imaging (NODDI). On global brain analysis, thicker ppRNFL, GC‐IPL and GCC were all significantly associated with patterns of diffusion metrics consistent with higher WM microstructural integrity. In regional analyses, after multiple testing corrections, our results suggested significant associations of some retinal nerve layers with brain regional gray matter occipital volumes and with diffusion MRI parameters in a region involved in the visual pathway and in regions containing associative tracts. No associations were found with global volumes or with global or regional cortical thicknesses. Results of this study suggest that some retinal nerve layers may reflect brain structures. Further studies are needed to confirm these results in young subjects. In a sample composed exclusively of young healthy subjects, we found significant associations between retinal nerve layers with occipital brain volumes, and with brain diffusion MRI parameters, globally and in regions containing associative, commissural tracts, and in a projection area involved in the visual pathway. Our results suggest common maturational processes in the retina and the brain. Further studies are needed to confirm these results and to study common factors that might explain the parallel maturation of the retina and the brain.